Missense Genetic Polymorphisms of Microsomal (EPHX1) and Soluble Epoxide Hydrolase (EPHX2) and Their Relation to the Risk of Large Artery Atherosclerotic Ischemic Stroke in a Turkish Population - Can Demirdöğen B (Dove Medical Press, 2021)
Birsen Can Demirdöğen,1 Yağmur Miçooğulları,2 Aysun Türkanoğlu Özçelik,3 Orhan Adalı4 1Department of Biomedical Engineering, TOBB University of Economics and Technology, Ankara, Turkey; 2Institute of Natural and Applied Sciences, Department of Biology, Middle East Technical University, Ankara, Turkey; 3Food Safety and Agricultural Research Center, Akdeniz University, Antalya, Turkey; 4Department of Biological Sciences, Joint Graduate Program in Biochemistry, Middle East Technical University, Ankara, TurkeyCorrespondence: Birsen Can DemirdöğenDepartment of Biomedical Engineering, TOBB University of Economics and Technology, Ankara, TurkeyTel +90 312 292 42 79Email birsencan.demirdogen@gmail.comPurpose: Soluble epoxide hydrolase (sEH) and microsomal epoxide hydrolase (mEH) both catalyze the metabolism of epoxyeicosatrienoic acids (EETs), lipid signaling molecules that are protective against ischemic brain injury owing to their participation in the regulation of vascular tone and cerebral blood flow. In addition, mEH metabolizes polycyclic aromatic hydrocarbons, one of the causative factors of atherosclerotic lesion development. In this study, we aimed to investigate the association of enzyme activity-modifying missense single nucleotide polymorphisms (SNPs) of the sEH gene (EPHX2) and mEH gene (EPHX1) and ischemic stroke risk in a Turkish population.Patients and Methods: Genomic DNA of patients with large artery atherosclerotic ischemic stroke (n=237) and controls (n=120) was isolated from blood samples, and genotypes for Tyr113His (rs1051740) and His139Arg (rs2234922) SNPs of EPHX1 and Arg287Gln (rs751141) SNP of EPHX2 were attained by the PCR/RFLP method.Results: Minor allele frequency and genotype distributions for Arg287Gln, Tyr113His and His139Arg SNPs did not differ significantly between stroke patients and controls. However, hypertension- and diabetes-associated ischemic stroke risk was decreased by EPHX1 and increased by EPHX2 variants in stratification analyses.Conclusion: This study has shown for the first time that the polymorphic alleles of EPHX1 were unlikely to be associated with large artery atherosclerotic ischemic stroke susceptibility; however, protective effects were evident within subgroups of hypertension and diabetes. In addition, EPHX2 Arg287Gln polymorphism, which has been studied for the first time in a Turkish population, was not significantly related to ischemic stroke, but increased the stroke risk in subgroup analysis.Keywords: Arg287Gln, epoxyeicosatrienoic acids, EETs, His139Arg, SNP, Tyr113His